Customer satisfaction and brand loyalty towards online purchase store Amazon and Flipkart: An Empirical study. - Yadav, Anil Kumar; Zaman, Aminuz; Basumatary, Priyo (The journal of contemporary issues in business and government, 2021)
In the present scenario it is clearly known that customers are very smart and also had various options from different sellers with varieties of options for whatever products or service there are a large number of options are there with the customers so for the above issue mostly companies or seller are targeting more on creating loyal customers by providing better quality product or service at a reasonable rate which means they are giving more emphasis on satisfying the customers instead of mass products for increasing profits which were earlier used in the traditional marketing concept but now-a-days the trend is totally different and they only try to satisfy the customers. The study was conducted on customer satisfaction in relation to brand loyalty towards online selling application – Amazon and Flipkart. The purpose of the study was to examine various factors influencing brand loyalty and also to study the impact & satisfaction level of customer on brand loyalty by taking sample size as 400 from Guwahati city. The researcher has design descriptive and analytical structure for the purpose of the study. After analysing the data, it is find that mostly customers are influence by quality of the product or service which give them more satisfaction in comparison to other factors and also in times of price increase majority of the respondents are of the opinion that they never switch to other brands.